2012
DOI: 10.14411/eje.2012.054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pitfall trap construction and preservative on catch size, species richness and species composition of ground beetles (Coleoptera: Carabidae)

Abstract: Abstract. Pitfall trapping is the most frequently used sampling technique for epigeal arthropods. Trap design could significantly affect the catch so the results of studies using different trap designs may be difficult to compare. Although species composition is frequently investigated in ecological studies, however when pitfall trapping is employed, the effect of trap design on the recorded species composition is rarely considered. In the present study, we investigated the effect of trap construction (funnel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The abundance of troglobionts gradually increased until the summer peak, and progressively decreased afterwards, indicating that the sampling itself did not crucially affect the outcomes. However, aside from sampling techniques, such as the trapping design (e.g., Brown & Matthews, ; Knapp & Růžička, ), other potential sources of error have not been addressed. For example, the composition of cave communities varies from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of troglobionts gradually increased until the summer peak, and progressively decreased afterwards, indicating that the sampling itself did not crucially affect the outcomes. However, aside from sampling techniques, such as the trapping design (e.g., Brown & Matthews, ; Knapp & Růžička, ), other potential sources of error have not been addressed. For example, the composition of cave communities varies from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…The specific assumption about the degree of directional persistence influences the simulated movement pattern of ground arthropods and, thus, affects the probability of a “trapping event” and the sampling bias, which concerns the purpose of our study (see empirical model parameterization in Appendix ). Emergence: A trapping event, and thus the number of sampled individuals, emerged purely from the movement of ground arthropod individuals across the simulated area with pitfall traps integrated. To limit side‐effects of the specific position of each individual at simulation start, each simulation experiment with a particular parameter set was repeated 50 times and results were averaged for model analysis. Interaction: No interactions were considered among ground arthropod individuals or between ground arthropod individuals and pitfall traps, such as repelling or attraction due to preservative type in the trap (simplifying findings from Knapp and Ruzicka and Brown and Matthews ). Stochasticity: Some key processes of ground arthropod movement were modeled by assuming they are random and follow a certain probability distribution including speed, displacement, and turning angle (see probability distributions within Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…3. Interaction: No interactions were considered among ground arthropod individuals or between ground arthropod individuals and pitfall traps, such as repelling or attraction due to preservative type in the trap (simplifying findings from Knapp andRuzicka 2012 andMatthews 2016). 4.…”
Section: Trapping Event: An Individual Died and Wasmentioning
confidence: 99%
“…In fact, effective pitfall trap sizes have been numerously investigated for ground beetles (Knapp & Růžička 2012;Koivula et al 2012;Luff 1975;Obrist & Duelli 1996;Waage 1985;Work et al 2002) and other ground dwelling arthropods (Abensperg-Traun & Steven 1995;Brennan et al 1999Brennan et al , 2005. In general, larger traps perform better in collecting ground dwelling arthropods including ground beetles (Abensperg-Traun & Steven 1995;Brennan et al 1999Brennan et al , 2005Knapp & Růžička 2012;Koivula et al 2012;Luff 1975;Work et al 2002), while small-sized traps generally have low capacity to keep trapped arthropods before trap replacement (Luff 1975). However, no intensive studies for estimating biodiversity of ground beetles have been reported, which consider interaction effect between trap sizes and sampling duration.…”
Section: Introductionmentioning
confidence: 99%